PENELITIAN KOMUNIKASI PENDEKATAN KUALITATIF BERBASIS TEKS: APLIKASI MODEL SAUSSURE DAN MODEL PIERCE - Imran, Hasyim Ali (Istek Widuri Jakarta, 2015)
Based on the lack of knowledge about research with a qualitative approach, so as enlightenment efforts,especially for the students, this article focuses on the discussion of the practice of text analysis based onSaussure and Pierce Model. From the discussion, it is known that in practice both models each has stagesthat must be followed in order to ease in the research process. In order to further facilitate the process ofunderstanding in practice, it is necessary for students to practice once or twice against a different text,especially for Pierce models that are more complex than the model of Saussure.